ANALYSIS OF THE STATUS OF THE ISLAMIC STATE IN ISLAMIC ECONOMIC DEVELOPMENT A STUDY OF THE THOUGHTS OF ABDULLAHI AHMED AN NAIM : ANALISIS STATUS NEGARA ISLAM DALAM PEMBANGUNAN EKONOMI ISLAM TELAAH PEMIKIRAN ABDULLAHI AHMED AN NAIM - Khalida, Nur Diana; Fageh, Achmad (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
The need for reform of sharia and its methodological tools is based on the assumption that the existing position and formulation of sharia is considered inadequate and even considered contrary to the principles of modern law and human rights with current actual issues. Islamic economic development is also very important in modern countries even though it does not adhere to the Islamic system as a whole. The research method used by the author in this study is a qualitative research method using a literature study approach. Qualitative research is the collection of data on a natural background with the intention of interpreting the phenomena that occur. In qualitative research, of course, data such as words, pictures and others are collected, so that all data collected then allows it to be the key to what has been studied. Data in this study was sourced from books, journals and other scientific works. The problem in this study is related to aspects of Islamic economic development that are not only based on Islamic countries. The Islamic state in question is a system of government and other regulatory systems making Islam as a guideline as a whole